The effect of healthcare education program on diabetic patients post cardiac surgery - Shobian, Khlood Sameer; Abukhudair, Walid Abdulkareem; Alnajjar, Maher Mohammed; Rajab, Mussab Fayez (International Journal Of Community Medicine And Public Health, 2018)
Background: Health education and lifestyle modifications re as important as pharmacotherapy in management of diabetes mellitus. It is suggested that healthcare education would aid in controlling glycaemic measures among diabetic patients especially in critical situations during postoperative periods. The aim of this study was to explore the impact of healthcare education program on diabetic patients who underwent cardiac surgery in Jeddah. Methods: This was a prospective cohort study that was conducted in King Fahd armed forces hospital in Jeddah during the period 2009-2017 on 387 patients. Baseline Hemoglobin A1c was tested for all patients on regular basis (at 0, 3, 6, and 12 months), then a healthcare educational program was started followed by subsequent measurement of Hemoglobin A1c at the same time intervals. Comparisons between the Hemoglobin A1c before and after the program were made. Results: There were no significant differences as regards Hemoglobin A1c levels among the studied patients before and after healthcare education (p=0.087). However, on regression analysis, educational program establishment was significantly correlated with lower Hemoglobin A1c levels among the patients (OR=0.43 (0.32-0.49), p<0.0001). Conclusions: Healthcare educational programs can have a positive impact on improving Hemoglobin A1c control among diabetic patients after cardiac surgery.